Analisis Theory of Planned Behavior pada Perilaku Anti-Korupsi Mahasiswa Universitas Paramadina - Adrian Wijanarko; Mohamad Sajili (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This study aims to analyze the impact of counseling actions by Paramadina University students on changes in people s attitudes and behavior towards anti-corruption behavior. The research method used is descriptive qualitative and quantitative methods. The sample in this study were 107 respondents. The results of the research to foster people s attitudes and behavior are measured using three indicators, namely the variable behavior belief, normative belief, and control belief. The measurement results obtained on the belief behavior variable were 83.7 percent. Meanwhile, the normative belief variable indicator is 32.5 percent, and the belief control variable is 50 percent. So that the counseling action carried out to the community can run effectively and sustainably.